Clinical management of sex addiction - Carnes, Patrick 1944-; Adams, Kenneth M. 1948- (Routledge, 2020)
"Clinical Management of Sex Addiction's newest edition updates many of the original chapters from 28 leaders in the field with new findings and treatment methods in the field of sex addiction. With a growing awareness of sex addiction as a problem, plus the advent of cybersex compulsion, professional clinicians are being confronted with sexual compulsion with little clinical or academic preparation. This is the first book distilling the experience of the leaders in this emerging field. It additionally provides new chapters on emerging areas of interest, including partner counseling, trauma and sexual addiction, and adolescent sex addiction. With a focus on special populations, the book creates a current and coherent reference for the therapist who faces quickly escalating new constellations of addictive sexual behavior. Readable, concise, and filled with useful interventions, it is a key text for professionals new to field and a classic reference for all clinicians who treat sex addiction"--